An Evidence-based Recommendation for a Standardized Approach to Detecting Metastatic Neuroblastoma in Staging Bone Marrow Biopsies. (February 2017) - Parsons, LN; Gheorghe, G; Yan, K; Simpson, P; Jarzembowski, JA
Neuroblastoma is a common malignant tumor of childhood. Accurate bone marrow (BM) evaluation for metastatic tumor is essential; however, no standardized pathologic workup exists for staging BMs. We examined the diagnostic yield of various BM components and optimal core biopsy (CB) length as part of developing evidence-based recommendations for BM evaluation. After obtaining institutional review board approval, 160 BM biopsies from 50 neuroblastoma patients were retrospectively selected. Hematoxylin and eosin-stained CB and Wright-stained aspirates were scored as positive, negative, or indeterminate. Total/trabecular CB lengths were measured using cellSens software and a DP71 camera (Olympus). Of the 160 BMs, 72 were positive for tumor in any component. Of these, 33 (45.8%) were positive in a single portion of the specimen: 19 CBs and 14 aspirates. Compared with overall diagnosis, sensitivities were as follows: CB 76.3%; aspirate 67.1%; core/aspirate combined 94.7%. Diagnostic CBs had significantly longer trabecular length than nondiagnostic CBs (6.74 mm vs 4.03 mm, P = .006). Positive CBs had longer trabecular space than negative marrows (7.91 mm vs 6.25 mm, P = .002). Nearly 50% of our positive specimens showed diagnostic discordance among the various components examined. However, combining CB and aspirate examination improved sensitivity for tumor detection. We therefore recommend bilateral CBs (>1 cm each) and aspirates for the optimal evaluation of BM for metastatic neuroblastoma.